Realistic skin vs. flawless skin: explicating the appeal of retouch-free advertising among Chinese women - Yang, Tingting (2023)
Using retouched images of models in advertisements to embody idealized beauty prototypes (e.g., flawless skin) in various cultures has been a prevalent yet controversial practice. Guided by the overarching corporate moral responsibility framework, this study conducted two online experiments to assess the effects of ad retouching and disclaimers on advertising effectiveness. In Study 1, a 2 (model skin type: realistic skin vs. flawless skin) x 2 (retouch-free disclaimer: present vs. absent) between-subjects online experiment was conducted among Chinese female participants. The results revealed that Chinese female consumers’ preference for flawless skin still drives purchase intentions toward a skincare brand. However, when an ad employed a retouch-free disclaimer, participants who saw an ad depicting a model with realistic skin indicated higher ad honesty than those who saw an ad depicting a model with flawless skin. Consumers’ perceived ad honesty mediated the interaction effect between the model skin type and disclaimer on purchase intentions. In Study 2, we found a similar interaction effect and moderated mediation effects. Such that, when a retouch-free disclaimer was present, participants rated an ad featuring realistic skin to have significantly higher ad honesty than an ad featuring flawless skin, which in turn, led to higher purchase intentions. The findings provide theoretical and practical insights into how brands can better appeal to contemporary Chinese female consumers.